Future fuels for environmental sustainability: Roles of computing - Kasim H.; Omar R.; Hilme M.H.B.M.; Al-Ghaili A.M. (Science and Engineering Research Support Society, 2023)
In this review paper, a number of research studies related to future fuels have been analysed. There have been several studies introduced in order to highlight hazards of fuels produced by different types of transportation and their effects for the environment. Transportation is a vital enabler of human civilizations. Currently, the main fuel source use to power these various modes of transportation is fossil fuel. Two third of anthropogenic greenhouse gases (GHGs) emission originates from fossil fuel combustion in transportation and industrial sector. These GHGs particles are pollutants which have negative impact on the climate and the environment. To reduce these environmentally-harmful pollutants, people are looking into the use of alternative and renewable fuels. Information and Communication Technology (ICT) is regarded as a key instrument to create an efficient transportation system and networks. Therefore, resulting in less fossil fuel combustion. This in turn will curb climate change and reduce carbon footprints. This paper will also review the various roles of ICT in managing sustainability, environmental issues, and their impact on future fuels. This include technologies such as Artificial Intelligence, block chain, internet of things (IoT) and cloud computing. ICT solutions also enable the establishment of intelligent transportation systems and traffic networks. 2019 SERSC.